How liberalism assimilates minorities. The failure to develop a Welsh national movement in the nineteenth century - Simon Brooks (Studies on National Movements, 2014)
In the nineteenth century, Wales contained all the necessary building blocks for the development of a successful ethnolinguistic nationalism on the European pattern. However, no serious nationalist movement emerged, and that nationalism which did develop was civic rather than linguistic in nature. This course of events is explained by the unusual nature of the British state, and the development of ideologies within it. Britain was a liberal state, and Wales was the most liberal part of Britain. The emphasis of liberalism on personal advancement and individual emancipation came at the expense of communitarian loyalties. Inevitably, this undermined the idea of nation as an intellectual concept. Welsh radicals argued in sincerity for social justice, but justice could only be achieved on the basis of a common citizenship, which was shared with all in the British Isles and defined by the English language. Because of the liberal emphasis on shared civic space and cultural universalism, the Welsh attachment to radical politics led to cultural assimilation.